Algoritma Sequential Search Dan MD5 Pada Aplikasi Inventory Barang Berbasis Web - Doni Alfiyan; Septi Andryana; Ira Diana Sholihati (SMATIKA JURNAL : STIKI Informatika Jurnal, 2023)
Along with the development of IT companies began to utilize information systems. This technique makes it easier to find data so it is widely used. And also, if the data is stored using computerized techniques, the data information will be stored properly so as to avoid delays if you are still using a manual system. The system design method uses Agile software development. The programming language used to make the application is PHP, HTML, CSS, Javascript and the DBMS (Database Management System) used is MySQL. The source code is created using the Sublime text editor application. After creating the application, the next researcher conducted testing using the black box testing method. This goods inventory application was developed using the PHP programming language on a web-based platform to make it easier to access from various platforms that only require a browser. The Sequential Search and MD5 algorithms are implemented in a data search system and inventory in a warehouse that has security so that it makes it easier to search data, view stock of goods and company data is protected from people who are not prioritized so that it is more effective and efficient. The results of this study are that the existence of this inventory system application makes it easier in the storage process, reduces risks in the product search process and data security is more guaranteed.